A dual positive and negative regulation of monocyte activation by leukocyte Ig-like receptor B4 depends on the position of the tyrosine residues in its ITIMs. Issue 4 (May 2017) - Park, Mijeong; Liu, Robert W; An, Hongyan; Geczy, Carolyn L; Thomas, Paul S; Tedla, Nicodemus
The leukocyte Ig-like receptor B4 (LILRB4) is an inhibitory cell surface receptor, primarily expressed on mono-myeloid cells. It contains 2 C-type Ig-like extracellular domains and a long cytoplasmic domain that contains three intracellular immunoreceptor tyrosine-based inhibitory motifs (ITIMs). Data suggest that LILRB4 suppresses Fc receptor-dependent monocyte functions via its ITIMs, but relative contributions of the three ITIMs are not characterised. To address this, tyrosine (Tyr) residues at positions 337, 389 and 419 were single, double or triple mutated to phenylalanine and stably transfected into a human monocytic cell line, THP-1. Intact Tyr389 was sufficient to maximally inhibit FcγRI-mediated TNF-α production in THP-1 cells, but, paradoxically, Tyr337 significantly enhanced TNF-α production. In contrast, bactericidal activity was significantly enhanced in mutants containing Tyr419, while Tyr337 markedly inhibited bacteria killing. Taken together, these results indicate that LILRB4 might have dual inhibitory and activating functions, depending on the position of the functional tyrosine residues in its ITIMs and/or the nature of the stimuli.